Internship Model ’Freedom Learns Independent Campus’ for Nursing Students in the Digital Era of Industry 4.0 - Ponamon, Jolie Febri; Welong, Krety Debora; Naharia, Orbanus; Sumual, Shelty D.M. (International Journal of Information Technology and Education, 2023)
This research aims to develop and apply the Internship Model ’Freedom Learns Independent Campus’ (MBKM) specifically for nursing students in the digital era of Industry 4.0. This study acknowledges that the role of technology in nursing is increasingly important and that the use of technology in nursing student internships will increase their understanding of patient-centered health care. This study used a mixed approach involving both quantitative and qualitative methods. The research sample consisted of nursing students who are currently undergoing higher education programs and have access to digital technology. Data will be collected through surveys and interviews, which will be analyzed using statistical approaches and thematic analysis. The MBKM Internship Model will include the use of technology such as simulation, electronic data management, telemedicine, and mobile applications in the clinical practice of nursing students. Students will be given training in the use of these technologies and will have the opportunity to apply them in simulated and hands-on nursing situations. During the internship period, nursing students will work with clinical mentors who are experienced in integrating technology into patient care. They will be involved in the collection and analysis of clinical data using electronic data management systems, as well as conducting telemedicine consultations for guidance and feedback from experienced healthcare professionals. It is hoped that the results of this study will provide insight into the effectiveness of the MBKM Internship Model in preparing nursing students to face the challenges and opportunities offered by the digital era of Industry 4.0. In addition, the results of this study can become the basis for the development of curricula and nursing education programs that are more up-to-date and relevant to technological developments.